Pendekatan Humanistik-Religius dalam Pembelajaran Fikih di Madrasah Aliyah Negeri 3 Pontianak, Kalimantan Barat, Indonesia - Sukino Sukino; Erwin Erwin; Agus Maulidia (DAYAH: Journal of Islamic Education, 2020)
This research is motivated by the importance of a humanistic-religious approach that prioritizes the learning process rather than learning outcomes. While there are still many schools that do not understand the positive impact of this approach, so they still use the learning approach that focuses merely on students and learning outcomes. This study explains the humanistic-religious approach in Islamic Jurisprudence (Fiqh) learning. This research employed a qualitative approach in which data were collected through observations, documentation, and interviews. It was conducted at MAN 3 Pontianak, Indonesia, where teachers and students were research participants. This study found that Fiqh learning model with a humanist-religious approach is characterized by three main activities. First, fiqh learning is supported by learning implementation plan (RPP) documents that arranged systematically, describing the behavior of teachers and students who are full of responsibility, open, democratic, dynamic, and religious. Second, humanist class management is done by auditing the class and providing a broad collaboration space. Third, humanist religious approaches are also carried out by building reciprocal educational interactions through sharing learning methods or strategies.